Child Development - J. Patterson Charlotte (Mc Graw Hill, 2008)
Child Development brings the research to life through stories. What prompted researcher Virginia Apgar to develop what became the Apgar Test on newborns? Who knew that psychologist Eleanor Gibson' famous visual cliff experiment was inspired by her own toddler's experience of hesitation in approaching the edge of the Grand Canyon? These stories help students appreciate the relevance of theory, helping them internalize research-intensive material. Through integrating such stories, this text provides the scientific rigor of Berk's child development books from Allyn & Bacon with the accessibility of Worth's Berger.